Pengaruh Leverage, Kepemilikan Institusional, dan Intensitas Modal Terhadap Konservatisme Akuntansi - A. O, Irna Urba; Tanto, Tanto (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the effect of leverage, institutional ownership, and capital intensity on accounting conservatism in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative research method is utilized in this study, relying on secondary data from financial statements and annual reports of firms. A purposive sampling technique was utilized to determine the sample, considering criteria pertinent to the investigation goals. The number of samples utilized was 19 companies. This research utilized descriptive statistical tests, classical assumption tests, and multiple linear regression analysis in order to determine the effect of each independent variable on accounting conservatism. The outcomes of the study revealed that the leverage variable at a significance threshold of 0,788 > 0,05, signaling that leverage does not have a significant effect on accounting conservatism, while institutional ownership at a significance threshold of 0,015 < 0.05 signaling that institutional ownership has a significant negative effect, and the capital intensity variable at a significance threshold of 0,001 < 0,05 signaling that capital intensity has a positive effect on accounting conservatism.